Primary Culture of Mouse Neurons from the Spinal Cord Dorsal Horn - De-Li Cao; Peng-Bo Jing; Bao-Chun Jiang; Yong-Jing Gao (Bio-Protocol, 2017)
Primary afferents of sensory neurons mainly terminate in the spinal cord dorsal horn, which has an important role in the integration and modulation of sensory-related signals. Primary culture of mouse spinal dorsal horn neuron (SDHN) is useful for studying signal transmission from peripheral nervous system to the brain, as well as for developing cellular disease models, such as pain and itch. Because of the specific features of SDHN, it is necessary to establish a reliable culture method that is suitable for testing neural response to various external stimuli in vitro.